Understanding M. K. Gandhi’s Strategies of Communication through the Lens of the Sadharanikaran Model of Communication: A Study of Young India - Das , Srabani (Bodhi: An Interdisciplinary Journal, 2024)
This article presents a study of Young India in order to understand Mohandas Karamchand Gandhi’s strategies of communication. Using Adhikary’s Sadharanikaran Model of Communication (SMC) as a theoretical framework, it is focused on understanding Mahatma Gandhi as a communicator. He communicated with a large number of masses in a very effective way even at a time when the concept of mass media was not established in Indian society. Gandhi’s communication strategy is assessed by analysing his writings in Young India. It is observed that the communication strategy of Gandhi was dependent on India’s own culture and heritage.